2006
DOI: 10.1016/j.juro.2006.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Macroscopic Tumor Necrosis as a Prognostic Indicator for Renal Cell Carcinoma

Abstract: Our results suggest that macroscopic tumor necrosis may be a reliable prognostic indicator for nonmetastatic clear cell renal cell carcinoma which should routinely be examined for during pathological analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 16 publications
2
21
2
2
Order By: Relevance
“…In the majority of reports (16 out of 20) there was an association between the presence of tumor necrosis and poorer prognosis including reduced overall survival [16][17][18], reduced cancer-specific survival [8,13,15,[19][20][21][22][23][24][25] and increased risk of metastases or disease recurrence [26][27][28]. The largest study relating to RCC was undertaken by Sengupta and coworkers who examined the pathology of over 3000 patients and reported an increased risk of cancer death in patients with necrosis, even after making a djustments for tumor size, grade and stage [13].…”
Section: Tumor Necrosis In Renal and Transitional Cell Malignancymentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of reports (16 out of 20) there was an association between the presence of tumor necrosis and poorer prognosis including reduced overall survival [16][17][18], reduced cancer-specific survival [8,13,15,[19][20][21][22][23][24][25] and increased risk of metastases or disease recurrence [26][27][28]. The largest study relating to RCC was undertaken by Sengupta and coworkers who examined the pathology of over 3000 patients and reported an increased risk of cancer death in patients with necrosis, even after making a djustments for tumor size, grade and stage [13].…”
Section: Tumor Necrosis In Renal and Transitional Cell Malignancymentioning
confidence: 99%
“…In studies that had examined mixed histological subtypes of RCC, tumor necrosis was found to be of prognostic value only in clear cell tumors [13,19,21,24]. Indeed, necrosis has since been incorporated into an outcome prediction model for patients with clear cell RCC known as the tumor stage, size, grade and necrosis (SSIGN) score [8].…”
Section: Tumor Necrosis In Renal and Transitional Cell Malignancymentioning
confidence: 99%
“…Patard et al maintain that the histological subtype was a less powerful prognostic factor than the stage of the RCC (35). Tumor necrosis is also a widely accepted prognostic factor in RCC (36). Finally, the clinical prognostic factors include ECOG performance status, patient symptoms, cachexia and anemia (37).…”
Section: Discussionmentioning
confidence: 99%
“…In a Mayo Clinic study, histologic necrosis was associated with twice the risk of death from RCC compared with patients without necrosis [51]. Several studies also reported that the presence and extent of histologic necrosis in RCC were independent predictors of survival in localized but not metastatic cases [62,63]. Therefore, two outcome prediction models, SSIGN (stage, size, grade, necrosis) from the Mayo Clinic, and the postoperative outcome nomogram from the Memorial Sloan Kettering Cancer Center, have incorporated tumor necrosis in their models [27,64].…”
Section: Tumor Necrosismentioning
confidence: 97%